UJI RESISTENSI Mycobacterium tuberculosis TERHADAP OBAT ANTI TUBERKULOSIS (OAT) DENGAN METODE PENIPISAN (Life Science, 2013)
The purpose of this research is to find out the reaction of M. tuberculosis resistance to OAT whit dilution method. This research is exploration research with post randomized controlled design. Each sample made as suspension with Mc Farland 1 turbidity then experimented with PNB to detect Mycobacterium Other Than Tuberculosis (MOTT). Negative result of PNB experiment then resistance experimented. Resistance experiment grown in Lowenstein-Jeensen (L-J) medium as control and were mixed is L-J medium which had been added with each OAT that is Isoniazid 0,2 mg/L, Rifampisin 40 mg/L, Streptomisin 4 mg/L dan Etambutanol 2 mg/L. Experiment result of PNB shows that there are five negative sample and one MOTT positive sample. Resistance experiment with dilution shows that there are 5 sensitive samples to OAT. From the research it can be concluded that by dilution method is not really influencing M. tuberculosis resistance experiment to OAT.